Determinants of Value Creation in Indonesia's Sharia-Compliant Companies - Rizal Ma'ruf Amidy Siregar; Syafiq Mahmadah Hanafi; Abdul Qoyum (UPT Publikasi Ilmiah UNISBA, 2026)
This study examines the financial determinants of value creation in Indonesian Sharia-compliant companies by analyzing the effects of leverage, Current Assets to Total Assets (CATA), and Accounts Receivable to Total Assets (ARTA) on accounting-based and market-based performance, measured by Return on Assets (ROA) and Tobin’s Q. Panel data from firms consistently listed in the Indonesia Sharia Stock Index (ISSI) and Jakarta Islamic Index (JII) over the 2019–2023 period were analyzed using the Generalized Method of Moments (GMM) to address endogeneity and dynamic relationships. The results indicate that leverage has a significant negative effect on both ROA and Tobin’s Q, whereas ARTA positively influences ROA but has no significant impact on Tobin’s Q. CATA does not significantly affect either performance measure, while the lagged values of ROA and Tobin’s Q exhibit strong persistence, highlighting the dynamic nature of firm performance. This study contributes to the literature by integrating accounting-based and market-based measures of value creation within a dynamic GMM framework for Sharia-compliant firms and by incorporating Sharia governance principles into the analysis of financial performance. The findings extend stakeholder, firm value, and Sharia compliance theories by demonstrating that sustainable value creation depends on prudent financial management alongside adherence to Islamic principles. The results offer practical implications for managers, investors, and regulators seeking to strengthen the sustainability and competitiveness of Indonesia’s Sharia capital market.